Ants Nesting on Cecropia purpurascens (Cecropiaceae) in Central Amazonia: Influence of Tree Height, Domatia Volume and Food Bodies - Bonato, Vinícius; Cogni, Rodrigo; Venticinque, Eduardo Martins (Sociobiology, 2003)
Patterns of presence of ant colonies on Cecropia purpurascens CC Berg (Cecropiaceae) were investigated in central Amazonia. All individuals of C. purpurascens along a 14.3 km transect were searched for ants and their height, internode volume, and number of trichilia were recorded. Of the 50 C. purpurascens individuals studied, 32 (64%) were colonized by ants of four species: Azteca alfari Emery (Dolichoderinae) (N = 16), Camponotus balzani Emery (Formicinae) (N = 14), C. abdominalis (Fabricius) (Formicinae) (N = 1) and Crematogaster brasiliensis Mayr (Myrmicinae) (N = 1). Probability of C. purpurascens being colonized by ants increases with tree height, internode volume, and trichilium number. Of the three variables recorded, tree height was the most important in determining the presence of ants. Trees colonized by the two most common ant species (A. alfari and C. balzani) did not differ in height, internode volume, or number of trichilia. The patterns observed, the association between the identity of the ants and plant fitness, as well as the usefulness of this particular system for future studies are discussed.
Keywords: Azteca Alfari; Camponotus Abdominalis; Camponotus Balzani; Cecropia; Crematogaster Abdominalis; Crematogaster Brasiliensis; Dolichoderinae; Fabricius; Formicidae; Formicinae; Myrmicinae; Trichilia; Urticaceae